MENINGKATKAN KEMAMPUAN SISWA DALAM PERMAINAN REBANA MENGGUNAKAN METODE PEMBELAJARAN DRILL SMAS MUJAHIDIN PONTIANAK - yarso, Rizal; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed at improving the skill of playing tambourine by using the drilling method towards the 11th-grade students of social studies I in SMAS Mujahidin Pontianak. It was a collaborative class action research with a descriptive method. 35 of 11th-grade students were taken as the subject in this study. The data collection was conducted by using direct observation technique, whilst the student performance report was used as the data collection tool. The data were analyzed by the descriptive presentation. This study was conducted up to two cycles. The findings showed that there was an improvement in the students’ performance in playing tambourine. Cycle 1 showed the percentage of completeness with a value of 73,42%. Showing improvement in cycle 2 with the value of 85,85%, it comes to the conclusion that the students’ performance on playing the tambourines have improved. Therefore, the drilling method can improve the students’ skills in playing tambourines. Keywords: Ability, Drilling Method, Tambourine, Wasps